Factores de riesgo asociados a la hipertensión arterial en habitantes de la parroquia Mercadillo - Merizalde Dávila, Winston Gamaliel (2025)
There are several risk factors that are associated to High Blood Pressure (HBP), a pathology that is defined as the persistent elevation of systolic and/or diastolic blood pressure above values considered as normal. The objective of this study was to identify the prevalence and risk factors associated with high blood pressure in the residents of Mercadillo parish. The study was designed as quantitative, cross-sectional and descriptive research, for which a sample of 290 people, aged between 30 and 65 years old, was selected through stratified sampling. Data collection was carried out through a structured survey and direct blood pressure measurements. The results that were obtained are as follow: prevalence of arterial hypertension of 66.55%, being higher in women and in people over 41 years old. The main risk factors identified were sedentary lifestyle in 64.2%, alcohol consumption 62.8%, family and personal history: diabetes, overweight, HBP, stroke, cancer in 60.4%. In conclusion, there is a high prevalence of hypertension among adults in Mercadillo parish, accompanied by resilient risk factors